Define cyberspace security - Binxing FANG (网络与信息安全学报)
The booming development of the Internet brought unparalleled revolution to production and social life style,and the Internet itself has become the new driving force of economy in almost every country.However,It is embraced that not only development opportunities,but also enormous security challenges in the cyberspace.So as to enhance the healthiness of cyberspace and social form,every state and nation is actively promoting the construction of cyberspace security system and in-depth research of key technologies.A comprehensive view of cyberspace security development status was provided in the globe and in major areas,with systematic analysis on its core elements as well as the hierarchical model.